2016
DOI: 10.3390/ani6010004
|View full text |Cite
|
Sign up to set email alerts
|

Food Deprivation, Body Weight Loss and Anxiety-Related Behavior in Rats

Abstract: Simple SummaryFood deprivation protocols are frequently used in behavioral studies. However, there is limited evidence as to when food deprivation compromises animal welfare. Regarding the refinement of experiments involving animals, this study investigated the effects of food deprivation on body weight loss and behavior in male and female rats. Sex difference in behavior and motivational state after food deprivation is the main finding of the study. The data highlights the need for tailored pilot experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 62 publications
0
27
0
2
Order By: Relevance
“…However, previous data suggest that exploratory behavior is separable from seeking food and acquiring information associated with environmental aspects (Pierre et al, 2001). In addition, food deprivation for up to 48 h seemed not to alter anxiety or depression behavior (Dietze et al, 2016; Hendriksen et al, 2015). Thus, the underlying mechanism and function of the influence of acute FR on locomotor activity require further assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous data suggest that exploratory behavior is separable from seeking food and acquiring information associated with environmental aspects (Pierre et al, 2001). In addition, food deprivation for up to 48 h seemed not to alter anxiety or depression behavior (Dietze et al, 2016; Hendriksen et al, 2015). Thus, the underlying mechanism and function of the influence of acute FR on locomotor activity require further assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased activity could not explain changes of the retention in the Y-maze, because the total number of arm visits showed no significant difference from the control. On the other hand, previous studies have found that food deprivation for 0-48 h had no effect on the distance traveled in an open field test (Dietze et al, 2016;Pierre et al, 2001). It was assumed that the duration of fasting positively correlates the response rate of animals (Moscarello et al, 2009).…”
Section: Weight Loss Indexmentioning
confidence: 95%
“…This suggests that astroglial plasticity is part of a process that adapts the olfactory signal to physiological fasting. Prolonged fasting is stressful, and fasting for 24 hr to 48 hr activates the HPA axis and increases blood corticosterone in rats, depending on strain and age (Dietze, Lees, Fink, Brosda, & Voigt, 2016;Rowland, 2007). Our 48 hrfasted rats lost 18% of their body weight, probably associated with activation of the HPA axis.…”
Section: Discussionmentioning
confidence: 99%
“…At complete starvation violations of metabolic processes are observed in rats: inhibition of anabolism and generalized increase in protein catabolism. This is clinically manifested by a symptomatic complex, characterized by abrupt weight loss, agitation, and then depression, decreased diuresis, negative nitrogen balance (Dietze et al 2016).…”
Section: Resultsmentioning
confidence: 99%